The Jain Temple - Temples of India Project Team (Jio Institute, 2024)
The Jain Temple consists of a mukhamandapa (open porch), mandapa (hall) and a garbhagriha (sanctum sanctorum) in plan. The garbhagriha has a multi-spired shekhari variety of shikhara (spire). Seen here is the west-facing elevation of the temple exhibiting its intricate carving details, especially on the wall. The temple is built in a variety of sandstone but the jangha (wall) is in a different polished stone variety, that looks similar to the granite variety.